Analisis Bentuk Tindak Tutur Berbahasa Bali Pada Teks Video TikTok @madewangi: Kajian Pragmatik - Putu Krisna Paramartha; Made Iwan Indrawan Jendra; I Made Wiradnyana; I Made Dian Saputra (Cetta: Jurnal Ilmu Pendidikan, 2026)
Balinese on social media reflects an important linguistic development because it functions not only as a means of communication, but also as a space for cultural expression in the digital era. Although speech act studies have been widely conducted, research on Balinese speech act forms in TikTok  video texts remains limited. This study aims to describe and analyze speech act forms in Balinese TikTok  video texts created by @madewangi. This study employed a descriptive qualitative approach using five purposively selected TikTok  videos as the data source. Data were collected through observation, note-taking, transcription, and translation, and were then analyzed pragmatically by examining the relationship between utterance forms and their communicative functions. The results show that, out of 49 analyzed utterances, 35 were direct speech acts and 14 were indirect speech acts. The dominance of direct speech acts indicates that communication in Balinese TikTok  videos tends to emphasize clarity of meaning so that it can be easily understood by viewers, while indirect speech acts appear as strategies of politeness, satire, or implicit intention. This study contributes to pragmatic studies by showing how Balinese is used in digital media as a linguistic practice that continues to carry social and cultural dimensions.